Amplification of Mutator Cells in a Population as a Result of Horizontal Transfer - Funchain, Pauline (American Society for Microbiology, 2001)
Mutator cells that lack the mismatch repair system (MMR(−)) occur at rates of 10(−5) or less in laboratory populations started from wild-type cells. We show that after selection for recombinants in an interspecies mating between Salmonella enterica serovar Typhimurium and Escherichia coli, the percentage of MMR(−) cells rises to several percent of the recombinant population, and after a second successive mating and selection, greater than 95% of the recombinants are MMR(−). Coupling a single cross and selection with either mutagenesis or selection for spontaneous mutants also results in a dramatic increase in MMR(−) cells. We discuss how horizontal transfer can result in mutator strains during adaptive evolution.